Clinical study of primary caesarean section in multiparous women in a tertiary care hospital - Samal, Rupal; Palai, Pallavee; Ghose, Seetesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The objective of this study was to find the incidence and indications of primary caesarean section in parous women and evaluate the maternal and perinatal outcomes there from. Methods: Prospective study of primary caesarean sections in parous women at our institute from June 2013 to May 2014 was done. Age, indications and the maternal as well as perinatal outcomes were analyzed. Data was expressed as number and percentage. Results: Out of 1124 caesarean deliveries, 68 primary caesareans in parous women were done. The most common age group was 21-30 years. The majority of parous women who underwent primary caesarean section, were para 2. Booked cases constituted the maximum number of such women at 97.1 % (n=66). In parous women undergoing primary caesarean section, the number of spontaneous onset of labour was significantly more than those undergoing induction of labour. The most common indication for caesarean section in this group of patients was fetal distress. There was no neonatal mortality or adverse maternal outcome. Conclusions: Fetal distress was the most common indication for primary caesarean section in the parous woman, although malpresentation also contributed significant numbers. Primary caesarean sections in women with previous vaginal deliveries, were not associated with any significant neonatal or maternal complications.